A Critical Stylistic Study of Selected Newspaper Reports of Clashes between Fulani Herders and Farmers in Nigeria - Dare, Samson Adeyeye; Oyeniran, Stephen (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
This paper examines media reports of the clashes between the Fulani herdsmen and farmers, using the framework of the Lesley Jeffries’ critical stylistics. The study aims to lay bare the ideological dimension of the reports and the linguistic devices encoding such ideologies.  The clashes as reported in the The Punch and The Guardian newspapers between 2016 and 2018 supply the data for the study. The newspapers are selected based on their perceived wide circulation and readership. Twenty news reports, ten each, are randomly selected for analysis. The tools such as naming, equating and contrasting are employed to analyse the data. Noun phrases and nominalised verbs such as Fulani gunmen , killer - herdsmen , assailants , invaders construct the society’s worldview about the Fulani herdsmen. Some material action intention [MAI] verbs such as swooped, spewed, killed convey the deliberateness of cruel activities of the Fulani herdsmen. Different types of speech quotes, particularly direct speech [DS], also serve as a tool of the speech presentation of the participants in the texts, a device that is likely to implant the opinions of the participants in the reader’s mind. Equating and contrasting serve as a device to establish the society’s belief about the kind of equivalence and opposition that exist between the participants in the texts, while certain subordinate rankshifted clauses serve to foreground the writers’ main priority in the texts. This paper concludes that the critical stylistics analytical approach enhances the reader’s understanding of the hidden ideology embedded in the media texts. Keywords: Critical Stylistics, Crisis, Fulani Herdsmen, Farmers, Media Ideology